Outcome and Impact Based Evaluation of Research Program Implementation: A Case of Indonesian Public Research Institute - Wati Hermawati; Ishelina Rosaira; Radot Manalu; Agus Santoso; Saut Siahaan (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
This paper relates to outcome and impact based evaluation (OIBE) of a research program implementation at an Indonesian public research institute (PRI) ‘A’. The major funding for PRIs in Indonesia comes from government. It is very essential therefore, for variuos parties including policy makers to be informed about meaningful and relevant evaluation of the outcome and impact of such PRIto the welfare of the people, to technology development and innovation, and to the policy improvements in significant ways. The mixed-method with good blend of qualitative and quantitative analysis is used in the case study of a competitive research program (CRP) of PRI ‘A’. The case study demonstrates that the outcomes and impacts of CRP are found in the form of economic, social, and environment improvements in the communities; managerial change and innovation of technology and process for SMEs as well as improved existing policies; and increased capabilities of researchers at PRI. Recommendations of this study is that PRI’A’ should improve their research management and policy, strengthen collaboration with firms, including more human resources mobility is required to facilitate research collaborations and co-production process, and to have clear guidelines and targets of outcomes and impacts for their research results.Keywords: outcome, impact, Public Research Institute, evaluation, Indonesia